A Round-Robin based Load balancing approach for Scalable demands and maximized Resource availability (International Journal of Engineering and Computer Science, 2016)
In a communication scenario where the capacity of one running service is not enough to serve high demands and it is desired to increase the performance by distributing the workload across multiple resources i.e. services. The solution for such scenarios could be using of load balancer. Load balancer receives hundreds of requests at same instant from client and it distributes the load to the different instances/machines. This Load distribution is independent of the number of instances/machines. To simulate the scenario, this research implements a client application using a service to Sort the n numbers. The calculation is split into many small intervals. Therefore, the service gets overloaded and the performance drops down. In this research, a load balancer is proposed based on the Round-Robin approach. The service processes the message and sends back the response that is routed via the load balancer back to the client. Due to any reason if one of the instance/machine fails during process execution, this does not lead the complete process to failure. The Round-Robin approach is suitable for load balancing because the processing of requests takes approximately same time.